2013
DOI: 10.1007/s00520-013-1795-6
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal associations between caregiver burden and patient and spouse distress in couples coping with lung cancer

Abstract: Purpose While spouses play a vital role in the care of cancer patients, caregiving exerts a physical and psychological toll. Caregiving burden may not only compromise spouses’ quality of life but also the quality of care and support they are able to provide. Consequently, spousal caregiving burden may also negatively impact patients’ psychological adjustment. However, the effect of caregiving burden on patients’ psychological distress is unknown. Thus, this 6-month longitudinal study examined the associations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
115
4
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(136 citation statements)
references
References 43 publications
14
115
4
1
Order By: Relevance
“…Furthermore, our participants reported higher levels of financial problems as a result of caring than other informal caregivers [50][51][52]. These results may be attributed to caregivers in our sample being younger and having less life experience than informal caregivers in other studies [50][51]53] or, as suggested in other studies, a result of exhausting personal savings, reductions in income from reducing or terminating paid working hours in order to provide care [54], or Veteran's impulsive spending habits that can affect family finances. Mean subscale scores for caregiver self-esteem were similar to scores of spousal caregivers of patients 3 yr after stroke [51] and caregivers of lung transplant candidates [32].…”
Section: Discussioncontrasting
confidence: 32%
“…Furthermore, our participants reported higher levels of financial problems as a result of caring than other informal caregivers [50][51][52]. These results may be attributed to caregivers in our sample being younger and having less life experience than informal caregivers in other studies [50][51]53] or, as suggested in other studies, a result of exhausting personal savings, reductions in income from reducing or terminating paid working hours in order to provide care [54], or Veteran's impulsive spending habits that can affect family finances. Mean subscale scores for caregiver self-esteem were similar to scores of spousal caregivers of patients 3 yr after stroke [51] and caregivers of lung transplant candidates [32].…”
Section: Discussioncontrasting
confidence: 32%
“…Understanding the role of resilience in the relationship between coping and distress at a dyadic level can be also beneficial to health care practitioners and encourage the application of strength- and couple-based approaches to improve psychosocial adaptation among cancer survivors-spouses dyads. Given that caregiving burden undermines the long-term psychological adjustment of spouses and to some extent cancer patients [34], supportive care programs that are effective to manage spouses’ burden and cope with their stress may be also necessary in reducing psychological distress.…”
Section: Discussionmentioning
confidence: 99%
“…As the patient’s cancer and treatment-specific symptoms increase, patients’ and caregivers’ distress levels also increase, 11 caregiver physical and psychological health are negatively impacted, 1215 and caregivers' depression and burden increases. 16 Caregiving-related health problems cause further distress within the patient-caregiver dyad 17 and caregiver depression is likely to have a direct influence on patient outcomes. 1824 For instance, a patient's fear of recurrence at 3 months post-diagnosis is predictive of a caregiver’s increased distressed over time.…”
Section: Family Caregiving and Communicationmentioning
confidence: 99%